Tai Chi exercise improves working memory capacity and emotion regulation ability - Wang, Yi; Tian, Jing; Yang, Qingxuan (Frontiers in Psychology, 2023)
Purpose The study aimed to research the promoting effects of Tai Chi exercise on working memory capacity and emotional regulation ability among college students. Methods Fifty-five participants were recruited and randomly divided into the Tai Chi group and control group. The Tai Chi group had a 12-week Tai Chi training to implement intervention, while the control group performed non-cognitive traditional sports with the same exercise intensity as the Tai Chi group. The visual 2-back test of action pictures and the Geneva emotional picture system test were performed before and after the trial, which aimed to examine whether the action memory of Tai Chi training can improve individuals’ working memory capacity and emotion regulation ability. Results After 12 weeks, a significant difference was observed in Accuracy Rate (AR) (F = 54.89, p ≤ 0.001) and Response Time (RT) (F = 99.45, p ≤ 0.001) of individuals’ Visual Memory Capacity between the Tai Chi group and the control group. Significant effects in Time (F = 98.62, p ≤ 0.001), Group (F = 21.43, p ≤ 0.001), and Interaction (Groups × time; F = 50.81, p ≤ 0.001) on Accuracy Rate (AR) of the Visual Memory Capacity were observed. The same effect was observed again on the Response Time (RT) of the Visual Memory Capacity, Time (F = 67.21, p ≤ 0.001), Group (F = 45.68, p ≤ 0.001), Interaction (groups × time; F = 79.52, p ≤ 0.001). Post-hoc analysis showed that at the end of 12 weeks, the participants in the Tai Chi group had significantly higher Visual Memory Capacity than those in the control group (p < 0.05). After 12 weeks, valence difference (F = 11.49, p ≤ 0.001), arousal difference (F = 10.17, p ≤ 0.01), and dominance difference (F = 13.30, p ≤ 0.001) in the emotion response were significantly different between the control group and the Tai Chi group. The effect of valence differences in Time (F = 7.28, p < 0.01), Group (F = 4.16, p < 0.05), and Time*Group (F = 10.16, p < 0.01), respectively, was significant in the Tai Chi group after 12-week intervention. Post hoc analysis showed valence swings in the Tai Chi group were significantly lower than that in the control group (p < 0.05); The effect of arousal difference in Time (F = 5.18, p < 0.05), Group (F = 7.26, p < 0.01), Time*Group (F = 4.23, p < 0.05), respectively, was significant in the Tai Chi group after 12-week intervention. Post hoc analysis showed arousal fluctuations in the Tai Chi group was significantly lower than that in the control group too (p < 0.01); As the same, the effect of dominance differences in Time (F = 7.92, p < 0.01), Group (F = 5.82 p < 0.05) and Time*Group (F = 10.26, p < 0.01), respectively was significant in the Tai Chi group. Dominance swings in the Tai Chi group were significantly lower than that in the control group (p < 0.001). Conclusion The data support our speculation that action memory training in Tai Chi exercise may improve individuals’ working memory capacity, and then improve their emotion regulation ability, which has provided insightful information for customized exercise programs for emotion regulation in adolescents. Thus, we suggest those adolescents who are experiencing volatile moods and poor emotion regulation attend regular Tai Chi classes, which could contribute to their emotional health.